Student Gestures when Solving Local Wisdom-Based Mathematics Problems - Putri, Reta Eksa; Sulisawati, Dwi Noviani; Putra, Eric Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
When solving math problems, students make spontaneous movements called gestures. The purpose of this research is to find out the variations of gestures that appear when students solve math problems related to rotational geometry based on local wisdom. The qualitative approach used in this research is a descriptive research type. Test questions, documentation results, observations, and interviews were used as research instruments. The subjects of this study were four students in class XI for the 2022/2023 academic year at SMA Negeri Balung. The results showed that the group of students with high abilities used gestures more than students with low abilities. Students with high ability in solving math problems use 11 iconic gestures, 8 metaphoric gestures, and 24 deictic gestures. Meanwhile, the group of students with low abilities used 7 iconic gestures, 6 metaphoric gestures, and 12 deictic gestures. Based on the distribution of the number of student gestures when solving math problems, the gesture that appears the most is the deictic gesture, and the one that appears the least is the metaphoric gesture.